Parent Attachment dengan Kompetensi Sosial pada Remaja - Mardiana, Fita Indah Yustika Sari; Yulianti, Alma; Mukhlis, Mukhlis; Lestari, Yuliana Intan (Persepsi: Jurnal Riset Mahasiswa Psikologi, 2025)
Adolescents have mature social competence that will lead to behavior that is acceptable to society. This challenge is experienced by early adolescents and one of the influences is parent attachment in adolescents. This study aims to identify the positive relationship between parent attachment and adolescent social competence. This type of research is quantitative research. The subjects of this study were students of SMPN 40 Pekanbaru. A total of 240 students were targeted in this study. Research data were obtained using the Social Skill Scale with a reliability of 0.855 and the Inventory of Parent and Peer Attachment-Revised (IPPA-R) Scale with a reliability of 0.898. The R Square result is 0.60, stating that the parent attachment variable simultaneously contributes to social competence by 60%, while the remaining 40% is not studied. The results of Pearson's correlation analysis show that there is a positive relationship between parent attachment and social competence in adolescents, with a correlation coefficient of r=0.246. This means that the level of parent attachment is positively related to the level of social competence in adolescents. Thus the higher the level of parent attachment that adolescents have, the higher their social competence, conversely the lower the level of parent attachment that adolescents have, the lower their social competence. The implication of this study is that to improve social welfare and appropriate behavior accepted by society, adolescents have mature social competence by improving parent-attachment relationships.